Artes entre artes - Pérez Álvarez, David (Fonseca, Journal of Communication, 2021)
GONZÁLEZ GARCÍA, Fernando, CUNHA, Paulo y ROSÁRIO, Filipa (coords.), Procesos intermediales. Cine, literatura, espacio, Sial Pigmalión. Madrid, 2020, 295 pp.